Governo aberto: métricas para análise da aderência dos estados brasileiros aos princípios da Open Government Partnership - Peixoto, Julianne Fonseca (2019)
The Open Government Partnership - OGP is an international forum for dialogue and exchange of experience among governments, civil society organizations and the private sector on establishing accountable, transparent and the government at citizens' service. The expected benefits of openness are greater efficiency, integrity and legitimacy towards citizens. The OGP defines transparency, accountability, participation and technology as fundamental principles of open government, that is, as necessary conditions for their achievement. Thus, this research aims to analyze the adherence of Brazilian states to these principles. To this end, a composite indicator, the State Open Government Index, was elaborated, which brings together indicators related to each of these principles in a synthesis measure. In order to support the construction of the Index, a broad bibliographic and documentary review of the themes open government, transparency, accountability, participation, technology and evaluation metrics of governmental openness was carried out. Then the indicators were selected, standardized and agglutinated. As a result, it was found that none of the Brazilian states has “high adherence” to the principles of open government. On a scale from 0 to 1, the best result, 0.7212, was obtained by the Federal District and the worst, 0.3997, by Roraima. Thus, it is concluded that greater efforts are needed for the governmental opening of these entities, in order to obtain the expected benefits.